2003
DOI: 10.1103/physrevlett.90.237002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-Lattice Coupling to the Vortex-Melting Transition inYBa2Cu3O

Abstract: Distinct discontinuities in the thermal expansion of the crystal lattice are observed at the melting transition of the vortex lattice in a naturally untwinned reversible YBa(2)Cu3O(7-delta) single crystal using high-resolution dilatometry. This coupling between the vortex transition and the crystal lattice demonstrates that the crystal lattice is more than a mere host for the vortices, and it is attributed to a strong pressure dependence of the superconducting transition temperature and thus to the condensatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…and no melting anomaly could be detected below ≈ 3 K [see Fig. 3(c)] where only a broadened mean-field feature persists which in turn vanishes for T 0.7 K. Additional evidence for the existence of an underlying vortex-melting transition is obtained from thermal-expansion measurements, which have proven to be a very sensitive and complimentary probe of the vortex matter [27,30]. As shown in the heating curves (after field cooling) of Figs.…”
Section: (D) and 3(c)]mentioning
confidence: 99%
See 1 more Smart Citation
“…and no melting anomaly could be detected below ≈ 3 K [see Fig. 3(c)] where only a broadened mean-field feature persists which in turn vanishes for T 0.7 K. Additional evidence for the existence of an underlying vortex-melting transition is obtained from thermal-expansion measurements, which have proven to be a very sensitive and complimentary probe of the vortex matter [27,30]. As shown in the heating curves (after field cooling) of Figs.…”
Section: (D) and 3(c)]mentioning
confidence: 99%
“…Unequivocal thermodynamic evidence of a genuine vortexlattice melting transition finally came out soon after the discovery of the cuprate superconductors, in which thermal fluctuations are greatly enhanced due to their high-T c , very short coherence length and large anisotropy. In a very limited number of exceptionally high-quality single crystals, vortex melting manifests as a tiny discontinuity in the reversible magnetization [15][16][17][18], while heat-capacity [19][20][21][22][23][24][25][26] and thermalexpansion [27] measurements exhibit a peak superimposed on a step indicative of the additional degrees of freedom in the high-temperature vortex-liquid phase. This first-order transition represents the only genuine phase transition for superconductivity in a magnetic field, since H c2 (T ) becomes a broad crossover.…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 99%
“…These estimates yield for the universal ratios the values (23)). Recently it was shown that the melting line depends on pressure [50]. The underlying coupling between the vortex transition and the crystal lattice then demonstrates that the crystal lattice is more than a mere host for the vortices.…”
mentioning
confidence: 99%
“…1 In particular, studying the change in thermal expansion across a phase transition has become one of the important techniques in condensed matter physics since it can reflect the intrinsic change of the electronic system with very high resolution. [2][3][4][5][6] In the case of studying superconductors, the thermal-expansion measurement can detect phase transitions and vortex dynamics within the superconducting state, [7][8][9][10] which shows its unique advantages compared to resistivity and magnetic-susceptibility measurements. The ratio between the thermal expansion and the specific heat gives the Grüneisen parameter, which is a crucial thermodynamical parameter for studying quantum critical transitions.…”
mentioning
confidence: 99%